Pollinator movement activity influences genetic diversity and differentiation of spatially isolated populations of clonal forest herbs - Feigs, Jannis Till; Holzhauer, Stephanie I. J.; Huang, Siyu; Brunet, Jörg; Diekmann, Martin; Hedwall, Per-Ola; Kramp, Katja; Naaf, Tobias (Frontiers in Ecology and Evolution, 2022)
In agricultural landscapes, forest herbs live in small, spatially isolated forest patches. For their long-term survival, their populations depend on animals as genetic linkers that provide pollen- or seed-mediated gene flow among different forest patches. However, whether insect pollinators serve as genetic linkers among spatially isolated forest herb populations in agricultural landscapes remains to be shown. Here, we used population genetic methods to analyze: (a) the genetic diversity and genetic differentiation of populations of two common, slow-colonizing temperate forest herb species (Polygonatum multiflorum (L.) All. and Anemone nemorosa L.) in spatially isolated populations within three agricultural landscapes in Germany and Sweden and (b) the movement activity of their most relevant associated pollinator species, i.e., the bumblebee Bombus pascuorum (Scopoli, 1763) and the hoverfly Melanostoma scalare (Fabricus, 1794), respectively, which differ in their mobility. We tested whether the indicated pollinator movement activity affected the genetic diversity and genetic differentiation of the forest herb populations. Bumblebee movement indicators that solely indicated movement activity between the forest patches affected both genetic diversity and genetic differentiation of the associated forest herb P. multiflorum in a way that can be explained by pollen-mediated gene flow among the forest herb populations. In contrast, movement indicators reflecting the total movement activity at a forest patch (including within-forest patch movement activity) showed unexpected effects that are best explained by accelerated genetic drift due to enhanced sexual reproduction. This integrated approach revealed that bumblebees serve as genetic linkers of associated forest herb populations, even if they are more than 2 km apart from each other. It also showed that a higher within-forest patch movement activity of pollinators enhances sexual recruitment and thus diminishes the temporal buffer that clonal growth provides against habitat fragmentation effects.